Problematic Policy: Environmental Impacts of Traditional Mining in Papua - Hotlan Samosir (Hasanuddin Law Review, 2019)
Mining without permits has changed land cover in the mining area. The activities of people mining without permits have violated the principle of sustainable development, where the economic aspects take precedence over ecological and social aspects. The research is a normative-legal research using a statute, case and conceptual approaches. The research conducted in Nabire Regency, Papua, Indonesia. The results show that The activities of gold mining in Nabire regency which have been going on for decades have not been well-organized. The implementation of people mining has caused environmental damage, especially in the mining area. The environmental damage due to the weak role of Nabire government in terms of structuring efforts that began with the permitting process for the miners. The local government has the authority to establish regional regulations concerning people mining, so through this authority the management of people mining must be managed through permitting instruments. The authority of the permit only serves the local community as a participant after determining the rights and obligations of miners so that the implementation of people mining can be controlled by the local government by following the principles of sustainable development.